Screening for genetic variants in BDNF that contribute to childhood obesity. Issue 1 (16th January 2013) - Zegers, D.; Hendrickx, R.; Verrijken, A.; Van Hoorenbeeck, K.; Van Camp, J. K.; de, V.; Rooman, R. P.; Desager, K. N.; Massa, G.; Van Gaal, L. F.; Van Hul, W.; Beckers, S.
Summary What is already known about this subject BDNF is involved in the regulation of food intake and body weight. BDNF deficient animal models are obese. Chromosomal abnormalities cause obesity in humans. What this study adds Evaluation of point mutations in BDNF. Identification of BDNF mutations in obese children. Point mutations in BDNF are not a common cause of childhood obesity. Introduction There is ample evidence that BDNF has a role in the regulation of food intake and body weight. Study of various mouse models gave a clear indication that BDNF deficiency leads to the development of obesity. Functional loss of one copy of the BDNF gene, due to chromosomal rearrangements or microdeletions, can cause an obesity phenotype in humans. Therefore, we wanted to investigate whether point mutations in the gene also result in a comparable phenotype. Methods We screened 554 severely overweight and obese children and adolescents and 565 lean adults for mutations in the coding region of BDNF. Mutation screening was performed by high‐resolution melting curve analysis and direct sequencing. Results Screening of obese patients led to the identification of two synonymous variations (V37V and H65H) and two non‐synonymous coding mutations (T2I and V46M) in the BDNF gene. When we subsequently screened our control population, we found T2I with comparable frequency and confirmed that this is a rare and non‐pathogenic variant. In addition, we found another non‐synonymous mutation (N187S) in the control population. Conclusions In silico analysis of the V46M variant did not support a clear disease‐causing effect and no family data were available in order to determine whether the mutation segregates with obesity. However, we cannot rule out a possible pathogenic effect for this variant. In general, we tend to conclude that mutations in the coding region of BDNF are uncommon in obese patients and are therefore not likely to play an essential role in the pathogenesis of childhood obesity.